An Immigrant Paradox? Contextual Attainment and Intergenerational Educational Mobility - Feliciano, Cynthia; Lanuza, Yader R. (American Sociological Review, 2017)
Numerous studies have revealed a seemingly paradoxical pattern in which, despite cultural differences, unfamiliarity with the educational system, and possible language difficulties, children of immigrants outperform their peers with native-born parents in the U.S. educational system. We problematize the notion of an immigrant paradox in education by broadening our conceptualization of social class background, and introducing the concept of contextual attainment to capture the geographic and historical contexts in which education is completed. Analyzing nationally representative longitudinal survey data combined with international educational data, we show that, for immigrant parents, contextual attainments vary between and within countries of origin and often diverge from post-migration socioeconomic statuses. Parental contextual attainment helps explain why, net of standard family socioeconomic status measures, most groups of immigrants’ children complete more years of schooling than do White Americans with native-born parents. Moreover, considering parental contextual attainment leads to a rethinking of intergenerational educational mobility patterns for adults with immigrant parents. We argue that contextual attainment captures the noneconomic benefits of higher class background that help explain how intergenerational educational inequalities are reproduced.